Smart Contract as a New Instrument of Islamic Economic Diplomacy in the Blockchain Era - Kaslam, Kaslam; Amalthia Parah Rezky; A. Muhammad Fuad Ansari; Corana Chusnul Chatimah; Muhammad A'afi Azharan Fauzi (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
This article examines the role of smart contracts as an innovative instrument supporting Islamic economic diplomacy in the blockchain era. Blockchain technology, characterized by transparency, efficiency, and security, offers solutions aligned with the principles of Islamic economics, such as justice, honesty, and openness. The research aims to explore the potential use of smart contracts in accelerating international economic transactions compliant with Sharia law, while also identifying the challenges and opportunities for their global implementation. The study adopts a descriptive-analytical approach, combining secondary data from reports, case studies, and empirical analyses. One of the key findings is that smart contracts can streamline international trade and cross-border investment processes by reducing administrative costs, speeding up transaction settlements, and eliminating third-party risks. Case studies on the application of smart contracts in managing international zakat and halal investments demonstrate that this technology enhances trust and accountability among parties. The article also identifies several obstacles, including limited technological literacy, regulatory challenges, and cultural resistance in Muslim-majority countries. However, through collaboration between governments, private sectors, and international organizations, blockchain technology can be integrated into the framework of Islamic economic diplomacy to strengthen international relations. In conclusion, smart contracts represent a potential instrument to transform Islamic economic diplomacy, making it more relevant and competitive in the digital era. The study recommends developing Sharia-compliant technology regulations and promoting digital education as strategic steps toward integrating blockchain into the global Islamic economy.